2016
DOI: 10.5194/acp-16-3865-2016
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative potential of ambient water-soluble PM<sub>2.5</sub> in the southeastern United States: contrasts in sources and health associations between ascorbic acid (AA) and dithiothreitol (DTT) assays

Abstract: Abstract. The ability of certain components of particulate matter to induce oxidative stress through the generation of reactive oxygen species (ROS) in vivo may be one mechanism accounting for observed linkages between ambient aerosols and adverse health outcomes. A variety of assays have been used to measure this so-called aerosol oxidative potential. We developed a semi-automated system to quantify oxidative potential of filter aqueous extracts utilizing the dithiothreitol (DTT) assay and report here the dev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
284
6
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 262 publications
(335 citation statements)
references
References 85 publications
43
284
6
2
Order By: Relevance
“…The released OH radicals within particles or cloud droplets can oxidize other organic compounds, producing low-volatility products, including organic acids, peroxides and oligomers (Lim et al, 2010;McNeill et al, 2012;Ervens, 2015;Herrmann et al, 2015). Autoxidation in the condensed phase might be triggered by OH radicals forming highly oxidized compounds .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The released OH radicals within particles or cloud droplets can oxidize other organic compounds, producing low-volatility products, including organic acids, peroxides and oligomers (Lim et al, 2010;McNeill et al, 2012;Ervens, 2015;Herrmann et al, 2015). Autoxidation in the condensed phase might be triggered by OH radicals forming highly oxidized compounds .…”
Section: Discussionmentioning
confidence: 99%
“…The DTT assay is based on the decay of DTT due to redox reactions with PM components, reporting the oxidative potential of PM in moles of DTT consumed per unit of time and mass of PM. Verma et al (2015a) and Fang et al (2016) reported that PM 2.5 sampled in an urban environment in Atlanta, Georgia, USA, has a DTT activity in the range of 10-70 pmol min −1 µg −1 . Assuming an integration time of 20 min needed for the extraction of PM in this work, this value corresponds to (1-8) ×10…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%
See 3 more Smart Citations